Unintentional Injuries among Under-Five Children in Mid-Western Development Region, Nepal: A Cross-Sectional Study - Kafle, Bharat; Yadav, Uday Narayan; Marahatta, Sujan Babu; Mishra, Durga; Pant, Narayan Dutt (Journal of Nepal Paediatric Society, 2019)
Background: Unintentional injury is the biggest threat to survival of the under five children, which impact is immeasurable to families and often entire communities. This study aimed to estimate the prevalence of unintentional injuries among under-five children and the factors associated with it. Material and Methods: A facility based quantitative cross-sectional study was conducted between August to January, 2017. Multistage time frame convenient sampling method was applied to collect the data from 259 mothers of under-five children in selected district of Mid-Western Development region of Nepal. The data was collected from 10 rural health facilities and two from urban setting using semi-structured questionnaire. Analysis was performed using SPSS ver.15. Results: The prevalence of unintentional injuries was found to be 33.20 % among the under five children. The present study showed that ecological belt, age of mothers, education of mothers, education of father, occupation of mothers, occupation of fathers, family income quintiles, household type, numbers of sibling, age of the children and gender of children were significant factors associated with unintentional injuries among under-five children. More than 70% of the respondents were not aware how to provide first aid care to the children with respect to unintentional injury. Conclusion: This study highlights the burden of unintentional injuries among under-five children in mid-western development region of Nepal. Health education program in line with all type of fall injuries, burns and injuries with use of sharp objects might be helpful to tackle the problems.